Impact of macro-economic variables on all share price Index: an empirical evidence from Sri Lanka - Anandasayanan, S.; Subramaniam, V.A.; Gowsalya, S. (University of Jaffna, 2023)
Economic performance of a country highly depends on the macro-economic variables. l\iacroeconoinic variables are indicators or main signposts signaling the current trends in the economy. He general objective of this study is to investigate the impact of macro-economic variables on All Share Price Index in Sri Lanka. This study includes five key macro-economic variables namely, interest rate, inflation rate, unemployment rate, GDP growth rate and exchange rate. The annual data of twenty-five years from 1996 to 2020 were used for this research study. All companies listed in CSE are considered as samples. Data were analyzed using E-views version 10. Correlation analysis, Variable Inflation Factor, Unit root, OLS Regression and Heteroscedasticity Test were applied to identify the possible relationships among the variables and impact of macroeconomic variables on All Share Price Index. Correlation analysis reveals that there was a positive significant relationship between exchange rate and Al! Share Price Index. There is negative significant relationship between interest rate, inflation rate and unemployment rate, and all share price Index. The OLS regression analysis, established that the unemployment rate, interest rate have a negative significant impact on All Share Price Index, supporting the findings of Perera (2019). On the contrary the GDP growth rate has the positive impact on All Share Price Index. Moreover, the findings reveal that the inflation rates, and exchange rate do not have any significant impact on the All Share Price Index of Sri Lanka. The findings of the present study, helps the investors and portfolio managers to make effective investment decisions, because the knowledge on this inter-relationship between macroeconomic variables and share prices index provides a better understanding on portfolio performance. Similarly, the study is expected to offer some insights to financial regulators and policy makers in formulating economic and financial policies.
Keywords: Exchange rate; GDP growth rate; Inflation rate; Interest rate; All Share Price Index; Unemployment rate